Christianity and the rhetoric of empire : the development of Christian discourse - Cameron, Averil (Sather classical lectures, 1991)
Many reasons can be given for the rise of Christianity in late antiquity and its flourishing in the medieval world. In asking how Christianity succeeded in becoming the dominant ideology in the unpromising circumstances of the Roman Empire, Averil Cameron turns to the development of Christian discourse over the first to sixth centuries A.D., investigating the discourse's essential characteristics, its effects on existing forms of communication, and its eventual preeminence. Scholars of late antiquity and general readers interested in this crucial historical period will be intrigued by her exploration of these influential changes in modes of communication.